Microbiological Safety and Quality of Meals and Work Surfaces in Collective Catering Systems in Central Italy: A Five-Year Monitoring Study - Alessia Lupattelli; Sara Primavilla; Rossana Roila; Andrea Felici; Miriam Tinaro (Biology, 2022)
Ready-to-eat (RTE) meals produced and served by the catering system still represent one of the major causes of foodborne outbreaks, especially for susceptible consumers. Despite the great progress in food hygiene and safety, the systematic monitoring of microbial contamination of foodstuff is the most effective tool to ensure food safety and protect consumers’ health. The aim of this study was to perform a thorough assessment of the microbial safety and quality of meals and work surfaces of collective catering systems in central Italy, over a five-year period (2014–2018). In total 11,012 microbiological analytical determinations were performed in food matrices (80.1%) and environmental samples (19.9%). The results obtained show a low level of non-conformities ranging from 2.2% to 6.3% of total samples, concerning both hygiene and safety parameters. A decreasing trend of non-conformities during the years was also highlighted (p-value < 0.05), especially for environmental samples. This study suggests that the implementation of Good Manufacturing Practices (GMPs) and the proper definition of Hazard Analysis and Critical Control Point (HACCP) plans, combined with a thorough evaluation of microbiological monitoring, are able to ensure high levels of food safety and hygiene.